2023
DOI: 10.1158/1078-0432.ccr-23-0568
|View full text |Cite
|
Sign up to set email alerts
|

FDA Approval Summary: Axicabtagene Ciloleucel for Second-Line Treatment of Large B-Cell Lymphoma

Abstract: In April 2022, the U.S. FDA approved axicabtagene ciloleucel for adults with large B-cell lymphoma (LBCL) that is refractory to first-line chemoimmunotherapy or that relapses within 12 months of first-line chemoimmunotherapy. Approval was based on ZUMA-7, a randomized (1:1), open-label trial in 359 patients with primary refractory LBCL (74%) or early relapse who were transplant candidates. The study compared a single course of axicabtagene ciloleucel to standard therapy, consisting of chemoimmunotherapy follow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(1 citation statement)
references
References 16 publications
0
1
0
Order By: Relevance
“…Among those studied, 19 (31%; grade 3 in three) had neurological instances and 23 (38%; grade 3 in one) had cytokine release syndrome; there were no grade 4 events or deaths [122]. Another study found that 268 patients who received liso-cel as second-line therapy for large B-cell lymphoma experienced cytokine release syndrome (45%; Grade 3, 1.3%), as well as CAR-T cellassociated neurologic toxicities (27%) [123]. These findings urge for further assessment and preventive measures.…”
Section: Brexucabtagene Autoleucel Commonly Known Asmentioning
confidence: 99%
“…Among those studied, 19 (31%; grade 3 in three) had neurological instances and 23 (38%; grade 3 in one) had cytokine release syndrome; there were no grade 4 events or deaths [122]. Another study found that 268 patients who received liso-cel as second-line therapy for large B-cell lymphoma experienced cytokine release syndrome (45%; Grade 3, 1.3%), as well as CAR-T cellassociated neurologic toxicities (27%) [123]. These findings urge for further assessment and preventive measures.…”
Section: Brexucabtagene Autoleucel Commonly Known Asmentioning
confidence: 99%